Zycie pana Moliera - Bulgakov, Mikhail, 1891-1940. (Warszawa : Mlodziezowa Agencja Wydawnicza, 1987)
A fictional biography of the French playwrite Moliere.
Translation of: Zhizn gospodina de Molera.
Keywords: Moliere, -- 1622-1673 -- Fiction; Authors, French -- 17th century -- Fiction